THE ANTIDEPRESSANT ACTIVITY OF MUNTINGIA CALABURA L. LEAVES ETHANOL EXTRACT IN MALE SWISS-WEBSTER MICE - RAHAYUNINGSIH, NUR; FADHILA, SYIFA NUR; CAHYATI, KENI IDA (International Journal of Applied Pharmaceutics, 2022)
Objective: The purpose of this study was to determine the activity and optimal dose of Muntingia calabura L. ethanol extract as an antidepressant using Forced Swimming Test (FST), Tail Suspensions Test (TST), and Open Field Test (OFT). Methods: Twenty-five male Swiss-Webster mice were randomly divided into five groups. Group 1 as a control group, got vehicle (1% w/v CMC). As a positive control, group 2 got 0.052 mg/20 g mice BW of fluoxetine. Groups 3-5 received 0.7, 1.4, and 2.8 mg/20 g mice BW orally of M. calabura leaves extract. In the FST and TST, immobility time was the test parameter. In the OFT, the test parameters were the grooming duration, the duration of entries into the central square, and the duration of rearing. Results: The results showed that all test dose groups had antidepressant activity and test dose 3 was the optimal dose marked by a decreasing in immobility time in the FST and TST with an average percentage decrease of 33.70 % and 13.95%. In the OFT method, it is characterized by increasing in the average percentage of the duration of central square and rearing by 63.46% and 76.25%, respectively and a decreasing in the average percentage of grooming duration by 27.57%. Conclusion: From these results show ethanol extract of M. calabura leaves has antidepressant activity and the test dose of 3 (2.8 mg/20 g mice BW) is the optimal test dose.